TRANSPARANSI DAN AKUNTABILITAS LAPORAN KEUANGAN ORGANISASI KEAGAMAAN PADA GEREJA GPDI GLORIA MALANG - Hermanto Manto Anto; Hendrik Suhendri; Nur Ida Iriani (Cakrawala Jurnal Penelitian Sosial, 2021)
This research focuses on the transparency and accountability of the financial reports of religius organizatins at the GPDI Gloria church, Malang. Financial reports that are presented in a transparent and accountable manner are expected to provide a positive view of the congregation or donors to the church. The research method used by researchers is qualitative research methods, namely by describing the data obtained by researchers when conducting research or data obtained from the field. The data collection methods are interviews, observations and documentation which are of course related to the transparency and accountability of the financial reports of religious organizations at the GPDI Gloria church. The purpose of this study was to determine the transparency and accountability of financial reports as well as the management of financial reports in religious organizations. The results of this research are the GPDi Gloria church in its financial management and reporting has been transparent and accountable, but the recording and reporting still uses a recording system that is in accordance with what was obtained during bible school or in other words it has not applied the applicable financial recording and reporting standards, although thus they have tried to present it with transparency and accountability. Transparent and accountable financial reports will make it easier for the church to grow because it has won the trust of the congregation or donors.